Correction: Energy efficient gateway based routing with maximized node coverage in a UAV assisted wireless sensor network. - Bilal Ahmad; Masroor Ahmed; Nadeem Anjum; Masood Ur Rehman; Naeem Ramzan (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0295615.].